MAIN RESULTS OF THE PROJECT ‘MEDIEVAL PERM CIS-URALS: CHANGING POPULATION IN A CHANGEABLE ENVIRONMENT’ - Krylasova, N.B.; Bryukhova, N.G.; Korchagin, P.A. (Perm Federal Research Centre Journal, 2016)
Considerable results in studying economic and biosocial adaptation of the medieval population of Perm Cis-Urals were received within the framework of the Russian Foundation for Basic Research (RFBR) grant ‘Medieval Perm Cis-Urals: changing population in a changeable environment’. The novelty of the research was provided by a complex use of archaeological and anthropological methods, auxiliary historical disciplines, the humanities and natural sciences and GIS methods. For the first time for the territory under study historical, archaeological and anthropological data were compared with the results of natural-science analyses (palynological, carpological, radioisotopic, paleo-helmintological) as well as the results of linguistic (onomastic) research. A wide range of radiocarbon dates was obtained to specify the chronology of processes. According to the results of the work, a presentation with conclusions concerning the ecological situation on the territory of Perm Cis-Urals in the Middle Ages was introduced.